2016
DOI: 10.1093/jjco/hyw096
|View full text |Cite
|
Sign up to set email alerts
|

HDAC2 overexpression is a poor prognostic factor of breast cancer patients with increased multidrug resistance-associated protein expression who received anthracyclines therapy

Abstract: Objective: Previous studies have revealed the association of multidrug resistance with histone deacetylases inhibitors treatment in cancer cells. But little data were available for the correlation of histone deacetylases and drug-resistant-related proteins in breast cancer tissue. This study aimed to exploring the association of histone deacetylases expression with clinicopathological features, drugresistant-related proteins, prognosis and therapeutic responses in breast cancer patients. Methods: We performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 36 publications
1
22
0
Order By: Relevance
“…LINC01234 acts as a ceRNA to modulate CBFB expression in gastric cancer by absorbing miR-204-5p [33]. Herein, we uncovered a ceRNA mechanism of ARAP1-AS1-miR-2110-HDAC2 in BC cells, among which miR-2110 has been identified as an onco-suppressor in in neuroblastoma [34] and HDAC2 is a well-recognized transcriptional co-repressor that plays a carcinogenic role in BC progression [35][36][37]. In our research, miR-2110 overexpression inhibited cell proliferation, migration and stimulated cell apoptosis in BC.…”
Section: Discussionmentioning
confidence: 99%
“…LINC01234 acts as a ceRNA to modulate CBFB expression in gastric cancer by absorbing miR-204-5p [33]. Herein, we uncovered a ceRNA mechanism of ARAP1-AS1-miR-2110-HDAC2 in BC cells, among which miR-2110 has been identified as an onco-suppressor in in neuroblastoma [34] and HDAC2 is a well-recognized transcriptional co-repressor that plays a carcinogenic role in BC progression [35][36][37]. In our research, miR-2110 overexpression inhibited cell proliferation, migration and stimulated cell apoptosis in BC.…”
Section: Discussionmentioning
confidence: 99%
“…Other study reported that HDAC2 overexpression correlated with the metastasis, progression and the increased Ki67, multidrug resistance protein expression in breast cancer. 17 HDAC2 will remove acetyl groups from histones and creates a closed chromatin structure that prevents the transcription of genes involved in growth arrest, differentiation, and apoptosis. 11 The expression of PCNA is correlated with high cytological grading and poor prognosis in renal carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…The genes were ranked by the frequency of enrichments in biological process. Of the top 10 genes in HMLncs, nine were demonstrated to be associated with BRCA: FOXJ1 [ 31 ], HDAC2 [ 32 ], WNT1 [ 33 ], SOX18 [ 34 ], NOTCH4 [ 35 ], SP3 [ 36 ], HOXA11 [ 37 ], HOXC11 [ 38 ] and FOXD3 [ 39 ]. In addition, there were six genes coding transcription factors in the top 10 genes ( FOXJ1 , SOX18 , SP3 , HOXA11 , HOXC11 and FOXD3 ) (Figure 3E ).…”
Section: Resultsmentioning
confidence: 99%